Differential expression of cell surface sialoglycoconjugates on wild-type and cultured Ehrlich tumor cells as revealed by quantitative lectin-gold ultrastructural cytochemistry. - Roth, J (1994)
Three variants of the classical Ehrlich ascites tumor (EAT) cell have been studied by quantitative, sialic acid-specific, lectin-gold ultrastructural cytochemistry. Electron microscopic examination revealed pronounced differences in the surface morphology of the three cell variants. The wild-type Ehrlich cells (EAT-wt), grown in the peritoneal cavity of mice, exhibited a smooth surface profile. A variant form selected for growth as monolayer on basement membrane (EAT-c) showed a complex surface profile with numerous microvilli. The third variant (EAT-c/m), the cultured cells reinoculated into mice and passaged 20-25 times as ascites, presented a smooth surface profile similar to the EAT-wt cells. Quantitative single as well as double lectin-gold labeling revealed significant differences in the nature of cell surface sialoglycoproteins. The most significant finding was the presence of cell surface Neu5Ac alpha 2-6Gal residues as detected with the Sambucus nigra lectin on EAT-c and EAT-c/m cells, whereas EAT-wt cells contained little or none of such carbohydrate sequences. On the contrary, labeling by Maackia amurensis lectin, which recognizes the Neu5Ac alpha 2-3Gal beta 1-4GlcNAc sequence, was intense on all three Ehrlich cell variants; it was 20-60 times greater than alpha-2,6-linked sialic acid-containing glycoconjugates. Specific cell surface lectin binding combined with morphologic study appears to have identified a small subpopulation of cells within the ascites tumor that are capable of attaching to and growing on a basement membrane.